Fungal saprobes on dead leaves of Magnolia liliifera (Magnoliaceae) in Thailand - Promputtha I. (2014)
An investigation of saprobic fungi associated with dead leaves of Magnolia liliifera at Doi Suthep-Pui National Park, Chiang Mai, Thailand was carried out from June to September 2001. Ninety dead leaves fallen on the forest floor were collected and examined for fungi. Thirty-seven taxa of saprobic fungi comprising 20 ascomycetes and 17 anamorphic fungi (4 coelomycetes and 13 hyphomycetes) were discovered. Dominant species were Bionectria ochroleuca, Cylindrocladium floridanum, Dokmaia monthadangii, Gliocladium sp. 1, Hyponectria manglietiae, H. manglietiagarrettii, Hypoxylon sp., Lasiosphaeria sp., Pseudohalonectria suthepensis and Sporidesmium crassisporum which comprised 12.2%, 17.8%, 11.1%, 21.1%, 41.1%, 14.4%, 14.4%, 17.8%, 15.6%, 52.2% of the total collections, respectively. The diversity of fungi on this host is compared with that found in other studies.